Rezolvati ecuatia:
{ 2 x [ 14 + ( 5+x) :6 ] - 5 } :9 +7 = 10
Răspunsuri la întrebare
Răspuns de
5
Răspuns: x = 7
Explicație pas cu pas:
{ 2 x [ 14 + ( 5+x) :6 ] - 5 } : 9 +7 = 10
{ 2 x [ 14 + ( 5+x) :6 ] - 5 } : 9 = 10 - 7
{ 2 x [ 14 + ( 5+x) :6 ] - 5 } : 9 = 3
2 x [ 14 + ( 5+x) :6 ] - 5 = 3 × 9
2 x [ 14 + ( 5+x) :6 ] - 5 = 27
2 x [ 14 + ( 5+x) :6 ] = 27 + 5
2 x [ 14 + ( 5+x) :6 ] = 32
14 + ( 5+x) : 6 = 32 : 2
14 + ( 5+x) : 6 = 16
( 5+x) : 6 = 16 - 14
( 5+x) : 6 = 2
5 + x = 2×6
5 + x = 12
x = 12 - 5
x = 7
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă